Usulan Tempat Penyimpanan Tools untuk Mengurangi Aktivitas Motion di PT. XYZ - Pahlevi, Sinta; Suryadhini, Pratya Poeri; Oktafiani, Ayudita (Peneliti.net, 2024)
PT. XYZ is a manufacturing company engaged in the health industry, one of which is dental aerosol products. Based on the results of research directly in the production area, there are several problems that occur, namely finding the tools needed to carry out the production process, because the placement of tools is arbitrary, resulting in excessive movement of operators which causes non-value-added activities during the production process, and must be identified so that reduce non-value added activities. In the identification results using VSM and PAM, there are 67% non-value-added activities caused by searching activities in the production process. To reduce search activity in the production area, a tool storage area is proposed so that operators can pick up and carry tools in a special place. The simulation results using the FlexSim application after the suggestion that the search activity time can be reduced by 1467.14 seconds so as to reduce non-value added operator activities such as searching activities by 73%.